2016
DOI: 10.3892/etm.2016.3342
|View full text |Cite
|
Sign up to set email alerts
|

OPG rs2073617 polymorphism is associated with upregulated OPG protein expression and an increased risk of intervertebral disc degeneration

Abstract: The present study aimed to investigate the associations between three distinct osteoprotegerin (OPG) gene polymorphisms and the risk of intervertebral disc degeneration (IDD). A total of 200 IDD patients and 200 healthy controls were recruited from the Department of Spine Surgery at the First Affiliated Hospital of the University of South China (Hengyang, China) between January 2013 and May 2014. The allele, genotype and haplotype frequency distributions of three OPG polymorphisms in the study and control popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 55 publications
(57 reference statements)
2
22
1
Order By: Relevance
“…Although our study showed no, or only minor, effects of IL-1β on the expression of OPG by rat IVD cells, other studies have reported positive correlation between the grade of degeneration of human IVD tissues and OPG levels in IVD tissues [17] and serum [23]. Micro-environmental differences between human IVD tissues and rat cells cultured in vitro might also be responsible for this discrepancy between our study and others.…”
Section: Discussioncontrasting
confidence: 99%
“…Although our study showed no, or only minor, effects of IL-1β on the expression of OPG by rat IVD cells, other studies have reported positive correlation between the grade of degeneration of human IVD tissues and OPG levels in IVD tissues [17] and serum [23]. Micro-environmental differences between human IVD tissues and rat cells cultured in vitro might also be responsible for this discrepancy between our study and others.…”
Section: Discussioncontrasting
confidence: 99%
“…OPG is a member of the TNF receptor superfamily and has been found to be associated with IVD degeneration in mice and human tissue samples . Our findings of an association between OPG and DSN, indicative of IVD degeneration, are similar but slightly greater than those reported by Xue and colleagues using tissue sample confirmed IVD degeneration . In propensity score‐matched regression analyses (matched for age, sex, BMI, knee OA, and hip OA), we observed significant associations of OPG, IL‐6, and NPY with DSN.…”
Section: Discussionsupporting
confidence: 83%
“…Lumican, a proteoglycan that regulates collagen formation, may represent unique degradation properties of the IVD compared with peripheral joint osteoarthritis (OA) . In addition, recent pilot studies have identified inflammatory biomarkers, osteoprotegerin (OPG), interleukin‐17 (IL‐17), RANTES, and C‐X‐C motif chemokine ligand 6 (CXCL6) as significantly associated with lumbar spine IVD degeneration. Interleukin‐6 (IL‐6), an inflammatory cytokine, and neuropeptide‐Y (NPY), a neuropeptide involved in pain regulation and perception, have been also associated with cLBP .…”
mentioning
confidence: 99%
“…In a recent paper, Xue et al [24] showed that OPG serum levels were significantly higher in patients with intervertebral disc degeneration and the TC or CC genotype at the c.- 223C > T polymorphic locus (rs2073617) than those carrying the wild-type homozygous (TT) genotype. Earlier, Vidal et al [25] have proven an association between the c.-223T allele and lowered osteoprotegerin levels in blood serum.…”
Section: Introductionmentioning
confidence: 99%